As músicas veiculadas pelas mídias entre jovens: consumo, tendências e comportamentos - Gisele Maria Marino Costa (2015)
This thesis has its basis in Cultural Studies authors (García-Canclini, Otávio Ianni, Stuart Hall and Renato Ortiz) that has written about globalization, cultural globalization, the growth of global popular culture and how this can be related with education. It also explores PierreBordieus studies in Sociology of Education and the researches of Bernard Lahire with the purpose of reflecting on the following questions: how do teenagers consume the songs marketed by the media and how does this consumption can influence their experiences? This study analyzes the presence of the songs that are currently marketed by the media, its consumption by middle and high school students and how they can be related to the behavior of these teenagers, especially when it comes to their purchase decisions, with the purpose of thinking about the presence of music in the informal places of schools and also discussing the importance of musical education in this context. The research data has been generated by observations, interviews and focus groups that took place at one public and one private school of Belo Horizonte. This process had the purpose of learning which music genres were mostpopular among the students, how the process of choosing these genres works and how the songs are delivered to them. It was also analyzed how the music choices may be related to the students behavior and their consumption habits, and if music education programs at the schools can influence their musical preferences. During the process of collecting data, four instances of mediation were found (school, family, media and social group) and seven categories of analysis were created: music as a mark of personal life and subjectivity, music as a factor of creation and identity, music as social engagement, music and youth corporeality,music as an element of aesthetic enjoyment, music and consumption, music consumption, age and gender.The power of the songs marketed by the media is greatly increased and expanded by the easy access to them. They are present at schools on the students mouths, in theircellphones, Ipods, laptops, tablets and inside their minds, intermingled with the curriculum content and contexts, in the classrooms, halls and schoolyards. The relation between the world of media and the teenagers is an important part of their development and can influence the way they deal with the world. Faced with an expressive music consumption scenario, as seen with the students of both schools, educators must understand the habits of teenagers when it comes to informal music appreciation, in order to try to increase the repertoire and musicalculture of the students and to turn this into a process of informal learning in music.